-3(r+5)=-35

Simple and best practice solution for -3(r+5)=-35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(r+5)=-35 equation:


Simplifying
-3(r + 5) = -35

Reorder the terms:
-3(5 + r) = -35
(5 * -3 + r * -3) = -35
(-15 + -3r) = -35

Solving
-15 + -3r = -35

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + -3r = -35 + 15

Combine like terms: -15 + 15 = 0
0 + -3r = -35 + 15
-3r = -35 + 15

Combine like terms: -35 + 15 = -20
-3r = -20

Divide each side by '-3'.
r = 6.666666667

Simplifying
r = 6.666666667

See similar equations:

| 3x-1-9=0 | | -x+9=x+3 | | 115x+18x+7=180 | | s=2(s+3) | | 4x-32x+7=225 | | 2b^2-7b-9= | | 4x+43=x+16 | | 139=6x+6x+7 | | 2x+3(x+2)=126 | | 10+4y=30+y | | 15x+15+135x=180 | | 2t^2-8t+1=0 | | 2x=x+84 | | 8(3x+6)=6(4x+9) | | 9x+22=64 | | x+4(x+4)=66 | | Q-2.58=4.2 | | -3-24a=3a-3(2a-3) | | x/97+1042=9840 | | (5)10/(5)6= | | -7-(-4x)=9 | | x+4(x+4)=5 | | 2(x+x+2+x+4)=x+4 | | 3(3x+4)+63=13x+9-4x+66 | | x-4=5x+4 | | 3(2x+5)-2x=4(x+3)+3 | | -(-1.3-7p)=3.3+6p | | 2-2y=-22+y | | Blank+blank=936 | | -8x-3=-9x+4 | | x+2(x+4)=66 | | 8x+2x-17+10-5x+20=100 |

Equations solver categories